2019
DOI: 10.3390/s19112630
|View full text |Cite
|
Sign up to set email alerts
|

Design of UAV Downwash Airflow Field Detection System Based on Strain Effect Principle

Abstract: Accurate measurement of the downwash flow field of plant protection unmanned aerial vehicles (UAVs) is essential for analyzing the spatial distribution of droplets. To realize on-line rapid detection of the downwash flow field of a multi-rotor UAV, a flexible polypropylene detection device based on the principle of full bridge strain effect was proposed. Its performance principle was based on the physical deformation caused by wind pressure. The Fluid Flow and Static Structural modules of ANSYS 16.0 finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…For downwash effects, Yang et al [ 77 ] and Wu et al [ 78 ] reported airflow simulation results surrounding rotors. Both simulation results demonstrated that the downwash effects of the rotor bottom were large.…”
Section: Proposed Systemmentioning
confidence: 99%
“…For downwash effects, Yang et al [ 77 ] and Wu et al [ 78 ] reported airflow simulation results surrounding rotors. Both simulation results demonstrated that the downwash effects of the rotor bottom were large.…”
Section: Proposed Systemmentioning
confidence: 99%
“…Generally, the computational fluid dynamics of a bridge are calculated based on the finite element method [24][25][26][27][28][29][30][31]. For an incompressible fluid, the continuity equation and momentum equation can be expressed as [32]…”
Section: Computational Fluid Dynamicsmentioning
confidence: 99%
“…Naturally, these surface ripples are likely to propagate into the water and affect the vertical distribution of water column characteristics (e.g., physical, chemical, and biological properties) before water sampling can be carried out. Thanks to the development of pesticide spraying UAS, much research has been carried out to understand the effects of downwash from UAS rotors on land (Wen et al 2019; Wu et al 2019). However, downwash effects on water masses have not yet been evaluated.…”
Section: Figmentioning
confidence: 99%